Trans Papuan Highway Construction and Honey Eater Bird (Macgregoria pulchra) Population - Hartatik , Sri Een; Nisaa’, Ratri Ma'rifatun; Witasari, Lita; Fardhani, Indra; Widyati, Enny (Universitas Muhammadiyah Malang, 2023)
Lorentz National Park has a high degree of endemism; however, it is vulnerable to extinction. One of the most attractive birds is MacGregor’s Giant Honeyeater (Isap Madu Elok, Indonesian Language) that nested on the Dacryocarpus compactus tree. However, either the birds or the trees has very little information. On the other hand, they are impacted by the massive local development. Trans Papuan Highway Project crossing the Lorentz National Park area threat to the sustainability of habitat and population of that bird. This mini review highlights several impacts of road construction on the population of Isap Madu Elok bird in LNP: the habitat fragmentation; the potentially increasing human disturbance due to open access; and lastly the mitigation strategy for minimizing the impact.